PENGARUH LATIHAN PUSH UP TERHADAP DAYA TAHAN KEKUATAN OTOT LENGAN DAN BAHU ATLET ANGGAR PUTRA JUNIOR SIAK FENCING CLUB - Muhammad Zuhdi; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Purpose of This Research Is To Know The Effect Of Push Up Exercises Against Endurance of the Strength of Arm Muscles and Shoulder of Putra Siak Fencing Club's Junior Fencing Athletes. The purpose of this study was to find out whether there was the effect of Push Up Exercises on Endurance of the Strength of the Arm Muscles and the Shoulder of the Men's Junior Fencing Athlete Siak Fencing club.The data obtained as a result of the study are quantity data through tests before and after giving a test treatment for push up exercises. Data taken through tests and measurements of 6 Junior Boys Fencing athletes from Siak Fencing club. The variables in this study are push up exercises which are represented by X as independent variables, while strength durability is represented by Y as the dependent variable. Based on observations that researchers conducted with the trainers in club fencing, researchers looked and observed when athletes exercising or competing athletes were not maximally using the arm muscles resulting in weak punctures being inaccurate and easily deflected by opponents, opposition and movements easy to read by opponents. In the field of strength fencing, which is good according to Albertus Fenanlampir and Muhammad Muhyi Faruq (2014: 224) are 29 to 37 and 38 and above are very good categories. So the researchers gave a push-up test to find out the durability of the junior men's fencing athletes' club fencing power.Keywords: Push Up, Endurance of Arm and Shoulder Muscle Strength